ANALYSIS OF COST STRUCTURE AND COMPARATIVE INCOME OF OIL PALM AND COCONUT COMMODITIES ON SMALLHOLDER PLANTATIONS IN NORTH ACEH DISTRICT - Mawardati, Mawardati; Jullimursyida, Jullimursyida; Diana Chalil; Paramita, Loly; Razaki, Gus (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This research was conducted on oil palm and coconut plantation commodities in North Aceh Regency. The purpose of this study is to analyze the cost structure and the comparison of net income in the two businesses. The analytical methods used are cost analysis, net income, and Independent T-test analysis. The results of the analysis show that the production cost of oil palm plantations is higher than that of coconut. However, the results of the income analysis show that both businesses provide benefits to farmers and are feasible to work on. Furthermore, based on the results of the Independent T-test analysis shows that there is a significant difference in income/profits in the two businesses. The average income/profit of oil palm plantations is higher than that of coconut plantations due to the productivity and price of coconut being lower than that of oil palm. In addition, generally coconut farmers in the research locations directly market their coconuts after harvesting, and it is very rare for farmers to consider the selling price factor. Unlike the case with oil palm farmers, although the price of fresh fruit bunch fluctuates, it follows the standard price both between farmers and between regions. Oil palm farmers also often receive counseling from various parties, while coconut farmers in the research location have never received any counseling at all.